Fuzzy Logic Based Load Frequency Control of Hybrid Power System Integrated with SMES (International Journal of Innovative Research in Engineering & Management, 2022)
The use of a Fuzzy logic-based controller for  automatic generation control (AGC) and load frequency  control (LFC) of two area power plants in an interconnected  power system is proposed in this paper. In addition, a  superconducting magnetic Energy Storage (SMES) unit is  being considered in two areas. After a sudden load  disturbance, the implementation of SMES combination  arrests the initial fall in frequency deviation and tie-line  power deviation. The simulation results show that the  proposed SMES unit improves system performance  significantly. The system's sensitivity analysis is carried out  by altering the parameters and operating load conditions  from their nominal values. Even when the system is  subjected to wide variations in loading conditions and system  parameters, the optimised gains of the proposed fuzzy logic based controller and fuzzy controller along with SMES  controllers do not need to be reset. Finally, different types of  load patterns are used to test the effectiveness of the proposed  controller design. The simulation results show that the Fuzzy  PID controller combined with SMES outperforms the Fuzzy  PID controller alone. The simulations were run using the  MATLAB software.
Keywords: Conventional PID controller; fuzzy PID controller; oad frequency control; membership function; Inter-connected two-area system; Tie-Line power deviation